FORMATION OF MINANGKABAU YOUTH CAREER MATURITY THROUGH BALIAK KA SURAU CULTURE - Aulia Latifa; Firman; Riska Ahmad (Literasi Nusantara, 2021)
Career maturity of an individual can be influenced by external factors in the form of socio-cultural environment. The Minangkabau tribe is known for its culture of living in a surau for youth. Surau in Minangkabau besides having a function as a place of worship but also functions as a traditional Islamic educational institution not only to improve intellectual abilities but also to shape the character and personality of Minangkabau youth through religious learning activities, values of life, martial arts, communication skills. Then in the late 1950s, The existence of the surau in Minangkabau began to decline due to the PRRI incident in West Sumatra which caused psychological trauma for the Minangkabau community so that they began to leave their Minang identity, one of which was the culture of living in a surau. During the reform era, through Law no. 22 of 1999 Minangkabau again promoted the culture of living in a surau with the Baliak ka Surau movement. Where the technical implementation is relevant to the progress of the times in the 21st century. This study uses the library research method. The purpose of this paper is to present an analysis of how youth career maturity in Minangkabau is through the baliak ka surau culture. We need to preserve the Balinese culture of the surau considering the complex functions and benefits of the surau for Minangkabau youth.